2012
DOI: 10.1016/j.physletb.2011.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Norm-overlap formula for Hartree–Fock–Bogoliubov states with odd number parity

Abstract: A formula to calculate a norm overlap between Hartree-Fock-Bogoliubov (HFB) states with the odd number parity (one quasi-particle excited states) is derived with help of the Grassmann numbers and the Fermion coherent states. The final form of the formula is expressed in terms of a product of the Pfaffian for a neighboring even-even system (the zero quasi-particle state), and an extra factor consisting of the Bogoliubov transformation matrix and the anti-symmetric matrix in Thouless' HFB ansatz for the even-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…The proposal was largely inspired by the initial introduction of the Pfaffian idea by Robledo [30] to treat the sign problem in calculations of the overlap of Hartree-Fock-Bogoliubov (HFB) wave-functions. It was realized later [31][32][33][34][35] that the method can be applied to evaluation of general HFB matrix elements. The new Pfaffian method has turned out to be a feasible and very efficient algorithm for calculations with projected multi-qp states.…”
Section: Formalismmentioning
confidence: 99%
“…The proposal was largely inspired by the initial introduction of the Pfaffian idea by Robledo [30] to treat the sign problem in calculations of the overlap of Hartree-Fock-Bogoliubov (HFB) wave-functions. It was realized later [31][32][33][34][35] that the method can be applied to evaluation of general HFB matrix elements. The new Pfaffian method has turned out to be a feasible and very efficient algorithm for calculations with projected multi-qp states.…”
Section: Formalismmentioning
confidence: 99%
“…Many theoretical works followed Robledo's pioneering work [5][6][7][8][9] in order to extend Robledo's formula to multiple quasiparticle excited states. The extension essentially corresponds to finding a formula to evaluate a quantity such as…”
Section: The Pfaffian Formulaementioning
confidence: 99%
“…(9) can be easily evaluated as a special case of the formula derived in Ref. [7], where one-quasiparticle excited states are expressed as…”
Section: An Application Of the Pfaffian Formulae: Calculation Of ĥmentioning
confidence: 99%
See 1 more Smart Citation
“…In nuclear structure physics, the Pfaffian concept has been introduced [9] as a key mathematical tool for solving the long-standing problem in the phase determination of the Onishi formula [10]. Moreover, it has been shown that the Pfaffian algorithm is very efficient also for calculating overlap matrix elements [11][12][13][14][15][16]. In particular, by means of Fermion coherent states and the Grassmann integral, one can derive an alternative approach to calculate the rotated matrix element for general qp states [17], which serves as a theoretical framework to extend the PSM model space [18].…”
Section: Introductionmentioning
confidence: 99%